2002
DOI: 10.1016/s1472-6483(10)61810-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome mosaicism in cleavage-stage human embryos: evidence of a maternal age effect

Abstract: The present study evaluated mosaicism in a large series of cleavage-stage human embryos analysed by fluorescence in-situ hybridization. Only embryos with at least three cells analysed were included (n = 1235), of which 556 were mosaics. The most common types of mosaicism were chaotic (48%), diploid/polyploid (26%), and those caused by mitotic non-disjunction (25%). The number of abnormal cells per embryo ranged from 44% in diploid/polyploid to 84% in chaotic mosaics. Chromosome 16 was most commonly involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(110 citation statements)
references
References 43 publications
5
98
1
6
Order By: Relevance
“…However, in many of these embryos other cell lines are also present including polyploid, haploid and chaotic types. The available evidence suggests that aneuploid mosaicism detected at the cleavage stage is generated during one of the first three divisions, typically at the first or second division (Delhanty et al, 1997;Munné et al, 2002;Katz-Jaffe et al, 2004). Data from the 5-day-old embryos in the study by Daphnis et al, (2004) suggest that if the aneuploid cells arose during cleavage they are at a selective disadvantage compared with the diploid cells which have outgrown them.…”
Section: The Stage In Embryonic Development When Errors Leading To Anmentioning
confidence: 97%
“…However, in many of these embryos other cell lines are also present including polyploid, haploid and chaotic types. The available evidence suggests that aneuploid mosaicism detected at the cleavage stage is generated during one of the first three divisions, typically at the first or second division (Delhanty et al, 1997;Munné et al, 2002;Katz-Jaffe et al, 2004). Data from the 5-day-old embryos in the study by Daphnis et al, (2004) suggest that if the aneuploid cells arose during cleavage they are at a selective disadvantage compared with the diploid cells which have outgrown them.…”
Section: The Stage In Embryonic Development When Errors Leading To Anmentioning
confidence: 97%
“…It has been found that PGS especially benefits patients of advanced maternal ages, recurrent miscarriage and previous spontaneous miscarriage, as aneuploidy is the main reason for unsuccessful embryo implantation in these populations of patients [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PGD using polymerase chain reaction (PCR) can test for an increasing number of single gene disorders (Sermon et al, 2004) while PGD using fluorescence in situ hybridization (FISH) is used to determine gender in the case of Xlinked conditions or test for aneuploidy (Griffin et al, 1992;Delhanty et al, 1993). PGD for aneuploidy screening (PGDManuscript received 13 March 2006; accepted in revised form for publication by T. Liehr, 18 April 2006. having an increased number of aneuploid oocytes (Marquez et al, 2000;Munne et al, 2002;Wilton, 2002). PGD-AS represents an early form of prenatal diagnosis allowing identification and preferential transfer of chromosomally normal embryos.…”
mentioning
confidence: 99%